IMPLEMENTASI MODEL PEMBELAJARAN PBI (PROBLEM BASED INSTRUCTION) BERBASIS KPS (KETERAMPILAN PROSES SAINS) TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA MATERI LAJU REAKSI - Nur A’zizi (Program Studi Pendidikan Kimia, FKIP, Universitas Muhammadiyah Cirebon, 2019)
This research was conducted at SMA NEGERI 1 Jamblang which aims to find out how the implementation of the PBI (Problem Based Intruction) learning model based on KPS (Science Process Skills) on the critical thinking skills of students on the subject matter of the sub-material reaction rate the factors that influence the reaction rate Obtain more optimal learning outcomes and know the differences and increase in students' critical thinking skills by implementing the KPS-based PBI (Problem Based Instruction) learning model (Science Process Skills) on the reaction rate material, especially the factors that influence the reaction rate. The research design used in this study was the Pre-Test Post-Test Control Group Design. The research samples used in this study were class XI IPA 4 as an experimental class and class XI IPA 5 as a control class which was taken using purposive sampling technique. Data collection techniques for testing the implementation of the problem-based instruction model based on science process skills were obtained from the results of observations made by observers of researchers and students which were then processed into a percentage of implementation. While the data collection techniques for testing the differences in critical thinking skills of students were obtained from the Pre-Test and Post-Test which were then analyzed by the T test. by 96%. Keywords: Problem Based Instruction. Science Process Skills, Reaction Rate, and Critical Thinking Ability.